257 Young Scholar Presentation: Using an integrated systems biology platform to determine the mode of action of feed additives in nursery pig diets. (30th November 2020) - Trudeau, Michaela; Tran, Huyen; de Rodas, Brenda; Karnezos, Theodore; Gomez, Andres; Chen, Chi; Urriola, Pedro E; Shurson, Gerald C
Abstract: The mechanisms of action for antibiotic growth promotion are poorly understood, making it difficult to select effective alternatives that are capable of providing similar responses. In order to evaluate the complete impact of supplementing antibiotics and other feed additives to nursery pigs, an integrated systems biology platform encompasses the merging of traditional nutrition models with gut physiology, nutrition and omics technologies. The objective of this study was to evaluate the growth response, metabolic responses, and intestinal microbiome composition of nursery pigs fed antibiotics. Antibiotic diets containing chlortetracycline and sulfamethazine (AB), and diets containing no antibiotics (CON) were fed in 3 trials. Pigs were weighed at d 10, 21, and 42 post-weaning and ADG, ADFI, and G:F was calculated. On d 42, one pig/pen was selected for blood, cecal, and ileum content collection to assess metabolomic profiles via liquid chromatography-mass spectrometry. The composition of bacterial communities in those samples was determined by sequencing the V4 region of the 16s rRNA bacterial gene in the MiSeq platform. Metabolomics and microbiome data were analyzed using multivariate approaches and growth performance data were analyzed using a generalized mixed model. Pigs fed AB were heavier (P < 0.05) on day 42. There were also significant differences (P < 0.05) in the cecal and serum metabolite profile of pigs fed AB compared with CON. However, there were no changes in bile acid or short chain fatty acid concentrations in cecal samples when feeding AB. Although AB had no effect on alpha or beta microbiome diversity, the abundance of specific bacterial taxa shifted significantly (P < 0.05). These findings suggest that feeding antibiotics improve growth, alter metabolism, and affect the abundance of specific taxonomic groups of bacteria in the gut. In the future, this approach will be utilized to evaluate antibiotic alternatives for nursery pigs.